Hygiene Sanitation, Phisical Qualities and Bacterial in Fresh Cow's Milk of X Milk Company in Surabaya - Feryalin Navyanti; Retno Adriyani (JURNAL KESEHATAN LINGKUNGAN, 2015)
Abstract: Fresh cow's  milk consumed by many people so that the quality must be maintained so that people can safely consume. This study  was conducted to identify the state of hygiene and sanitation measures the quality of fresh cow's milk dairies  X in Surabaya.  This study  is a descriptive study,  with a cross sectional design. Data collection sanitary hygienic milk performed using observations corporate environment. Interviews  with owners and  cow  milker.  The existence Escherecia coli in fresh cow's  milk was tested by using the MPN method. The presence of the bacteria tested with Total Plate count  method. Physical quality is measured by means of sensory. The results  showed that the sanitation in the milk Milk Company X included in the category are not eligible. Variables that have  not met  the requirements of health and hygiene milker, cow  health and hygiene, health and hygiene cage. The quality of fresh cow's milk in terms of bacteriological content of escherechia coli negative while  for the  Total Plate Count  parameter ranges  5,4 í—  103 CFU/ml - 67,5 í— 104 CFU / ml. Physical qualities which include the color white, the typical smell of milk and sweetened slightly salty. The conclusion that can  be  drawn is sanitary hygiene while still qualify from the bacteriological quality, Total Plate Count parameters and the presence of Escherechia coli 01.3141.1998 meet the requirements of SNI and SNI 3141.01.2011. In order to improve  the quality of milk produced before milking cows should always be washed first and milked milk should be placed in containers or milk can is sealed to avoid contamination.Keywords: Total Plate count,  Escherichia coli, sanitary higiene of dairy milk